Senam Yin Yoga terhadap Penurunan Kadar Gula Darah pada Pasien Diabetes Mellitus Tipe II - Jayusman, Muhamad Ifadh Arifqy; Budiman, Budiman; Sitorus, Ria Eviyantini; Kosasih, Cecep Eli; Rumahorbo, Hotma (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to determine the effect of yin yoga on reducing blood sugar levels with type 2 diabetes mellitus in the Karawang Regency General Hospital. The method used in this research is quantitative with a quasi-experimental design, with a pre-posttest with a control design. The results of the study showed the results of the T-test (paired sample) showed that the average blood sugar level measurement before control was 334.95 mg/dl with a standard deviation of 95.697 mg/dl. The measurement value for the respondents' sugar levels after control was an average of 251.80 mg/dl. In conclusion, both blood sugar levels during pre-intervention and pre-control had similar results. Keywords: Diabetes Mellitus Type 2, Blood Sugar Levels, Yin Yoga Exercises